A comparison of acute mouse hindlimb injuries between tourniquet- and femoral artery ligation-induced ischemia-reperfusion. Issue 11 (November 2021) - Tu, Huiyin; Zhang, Dongze; Qian, Junliang; Barksdale, Aaron N.; Pipinos, Iraklis I.; Patel, Kaushik P.; Wadman, Michael C.; Li, Yu-Long
Highlights: Tourniquet/IR induced more severe skeletal muscle damage and contractile dysfunction, compared to femoral artery ligation/IR. Tourniquet/IR caused severe structural damage and functional loss in NMJs, while femoral artery ligation/IR induced mild impairment of NMJs. Tourniquet/IR caused significant tissue edema with high levels of proinflammatory cytokines, compared to femoral artery ligation/IR. Abstract: The tourniquet or femoral artery ligation is widely used to stop extremity hemorrhage or create a bloodless operating field in the combat scenario and civilian setting. However, these procedures with subsequent reperfusion also induce ischemia-reperfusion (IR) injuries. To fully evaluate animal models of limb IR injuries, we compared tourniquet- and femoral artery ligation-induced IR injuries in the hindlimb of mice. In C57/BL6 mice, 3 h of unilateral hindlimb ischemia was induced by placement of a rubber band at the hip joint or a surgical ligation of the femoral artery. The tourniquet or femoral artery ligation was then released, allowing for 24 h of reperfusion. Compared to the femoral artery ligation/IR, the tourniquet/IR induced more severe skeletal muscle damage, including muscle necrosis and interruption of muscle fibers. There was no gastrocnemius muscle contraction in tourniquet/IR, while femoral artery ligation/IR markedly weakened gastrocnemius muscle contraction. Motor nerve terminals disappeared, and endplate potentials (EPPs) were undetectable in tourniquet/IR, whereas femoral artery ligation/IR only induced mild impairment of motor nerve terminals and decreased the amplitude of EPPs. Additionally, western blot data showed that proinflammatory cytokine levels (IL-1β and TNF-α) were higher in the tourniquet/IR than that in femoral artery ligation/IR. Moreover, tourniquet/IR caused significant tissue edema and dilation of lymphatic vessels in the hindlimb, compared to femoral artery ligation/IR. The above data demonstrated that tourniquet/IR-induced acute hindlimb injuries are more severe than those induced by femoral artery ligation/IR. This suggests that future investigators should determine which hindlimb IR model (tourniquet/IR or femoral artery ligation/IR) is optimal depending on the purpose of their study.